THE INFLUENCE OF PRODUCT DEVELOPMENT AND PROMOTION TOWARD SALES VOLUME AT PT CIPTA LONA LESTARI MEDAN - Ali Syah Putra; Eddy, Eddy; Sri Aprianti Tarigan; Elyzabeth Wijaya; Agus Susanto (LPSDI Bina Patria, 2024)
The purpose of this study was to determine the effect of product development and promotion on sales volume at Cipta Lona Lestari Medan. This research is a type of quantitative research. The population in this study are all consumers who make purchases at the Cipta Lona Lestari Medan, the number of which is unknown. The sampling technique using the Lemeshow sampling technique obtained as many as 96 research samples. The method of collecting data in this research is literature study and questionnaires. Methods of data analysis using descriptive analysis and simple linear regression analysis. The results showed that the value tcount (2.909) > ttable (1.985) with a significance of 0.005 < 0.05 so it can be concluded that there is an influence between Product Development on the Sales Volume. The value of tcount (5.158) > tTable (1.985) with a significance of 0.000 < 0.05 so it can be concluded that there is an influence between Promotion on the Sales Volume. Simultaneous Testing Results (F-Test), the value of Fcount (62.621) > FTable (3.07) with a significant level of 0.00 < 0.05 so it can be concluded that H3 is accepted with the understanding that there is an influence between Product Development and Promotion on the Sales Volume